MUSICAL INCULTURATION IN MASS CELEBRATIONS IN THE CATHOLIC CHURCHES OF THE TOMOHON ARCHDIOCESE - Martinus Waruwu; Perry Rumengan (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aims to explore how the implementation of Musical Inculturation takes place during Mass in the Catholic Churches within the Tomohon archdiocese. Employing a qualitative descriptive method, data for this research is derived from interviews, photographs, and audio as well as video recordings. The theoretical framework encompasses musicology, music psychology, theology, ethnomusicology, and the Theory of PML, asserting that inculturation involves several stages, including translation, transition, adaptation, and the creation of new elements. The study substantiates that Inculturation in the Tomohon Archdiocese is widely embraced by the congregation, enhancing their faith, particularly during liturgical celebrations of the Mass. The infusion of culture into the liturgy deepens the congregation's connection with the divine, and according to the research findings and interviews with the congregation, it is evident that the presence of enculturated music in the Church has heightened the meaning of liturgical celebrations for the congregation. The enthusiasm among the congregation is notably high, and there is a consistent longing for the divine presence. The congregation expresses joy as the profound values of culture are accorded a special place in the Mass.